Increased inflammatory markers in adult patients born with an atrial septal defect - Schram, Anne-Sif Lund; Sellmer, Anna; Nyboe, Camilla; Sillesen, Martin; Hjortdal, Vibeke Elisabeth (Frontiers in Cardiovascular Medicine, 2022)
Patients with atrial septal defect have higher mortality and higher risk of atrial fibrillation, pneumonia and stroke than the general population. Recently, we described an increased burden of pathogenic gene variants in patients with an atrial septal defect. We speculate that inflammation may contribute to the association between atrial septal defect and morbidity and mortality. We investigated inflammatory activity in adults with an atrial septal defect compared with controls. We included 126 adults with an unrepaired atrial septal defect. A group of healthy controls were recruited as comparison group (n=23). Serum samples were analyzed for 92 inflammation-related protein biomarkers using a proximity extension assay. A pathway enrichment analysis was performed using Reactome database. Out of 92 biomarkers, 73 were eligible for data analysis. Increased levels of 14 (19%) biomarkers were found in patients with open atrial septal defect and 24 (33%) biomarkers in patients with spontaneously closed defects compared with controls (p<0.05). Multiple inflammatory pathways showed stronger enrichment in both patient groups when compared with controls. In conclusion, inflammatory activity is altered in adult patients with an unrepaired atrial septal defect compared with healthy controls. The increased inflammatory burden of patients with an unrepaired atrial septal defect may contribute to the development of morbidities.